Pengaruh PAD, Dana Perimbangan, dan Belanja Modal terhadap IPM di Provinsi Maluku Utara Tahun 2019 – 2023 - Tania Farah Fadilah; Avi Budi Setiawan (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The objective of this study is to investigate the impact of Regional Original Revenue (PAD), Balance Funds, and Capital Expenditure on the Human Development Index (HDI) in North Maluku Province from 2019 to 2023. The study is motivated by the difference seen between the growing fiscal capacity of the region and the relatively stagnant progress of HDI. Local governments are expected to efficiently utilize their financial resources under the framework of fiscal decentralization. A quantitative approach using a multiple linear regression model is used. Secondary data was obtained from the North Maluku Central Statistics Agency (BPS) and the Directorate General of Fiscal Balance (DJPK). The HDI is the study's dependent variable, and the independent variables are capital expenditure, balance funds, and PAD. The analysis includes the coefficient of determination (R2) and partial (t-test) and simultaneous (F-test) hypothesis testing. According to the results, capital expenditure, balance funds, and PAD all positively affect HDI. Capital expenditure and balance funds both make substantial contributions to HDI on their own, but PAD has no statistically significant impact. Capital Expenditure has the second-strongest impact on HDI among the three, after Balance Funds. These findings demonstrate how important regional spending and intergovernmental fiscal transfers are to raising living standards. The study comes to the conclusion that promoting human development in North Maluku Province requires focused financial investment in key sectors like social infrastructure, healthcare, and education.